Introducing eco-literacy to early childhood students through digital learning - Ninsiana, Widhiya; Septiyana, Linda; Suprihatin, Yeni (Journal of Education and Learning (EduLearn), 2024)
The objective of this study is to introduce eco-literacy in early childhood and to look into the role of digital media in increasing children's awareness of eco-literacy in the era of society 5.0 on daily environmental issues. This study applied a literature review of various sources related to eco-literacy through digital media, especially YouTube as well as interviewing class teachers. The results showed that introducing eco-literacy to elementary school students can be accomplished by telling stories, watching videos, or organizing field trips. There are four important points in developing an eco-literacy attitude: developing empathy, joining the community, making observable things visible, and asking children not to cause environmental damage. In addition to digital activities, efforts to improve ecological literacy should be extended through programs and exchanges regarding the need of environmental protection the 5R (refuse, reduce, reuse, recycle, and rot) approach. Further studies in the same topic on teaching eco-literacy to elementary school students can be carried out in a more intensive way through relevant games to instill a love of the environment based on 5R strategies.